ChemInform Abstract: Fused Catechol Ethers from Gold(I)‐Catalyzed Intramolecular Reaction of Propargyl Ethers with Acetals. Issue 29 (29th June 2016) - Pati, Kamalkishore; dos Passos Gomes, Gabriel; Harris, Trevor; Alabugin, Igor V.
Abstract: The title reaction proceeds under mild conditions following an alkyne activation/nucleophilic addition/alkoxyl group migration/cyclization/aromatization mechanism.